Turn-key courses for agricultural development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The Centre for Tropical Veterinary Medicine (CTVM) at the University of Edinburgh, UK, has developed teaching courses in a modular form. A module consists of one day of teaching over 10 weeks; students have to pass eight of these modules and submit...